Simulation of double-stranded branch point migration. - Robinson, B H (1987)
A structural and dynamic model has been developed for the branch point formed when two DNA double helices exchange strands during genetic recombination. This model, which generalizes most previous structural models, maintains the twofold symmetry inherent in the covalent and hydrogen bonded structure, yet has three degrees of freedom about virtual bonds, constituting a simplified junction. Using this structural model, a three-step dynamic model for branch point migration has been developed: longitudinal diffusion about the virtual bonds to achieve a structure in which the helix axes are approximately parallel; opening of the base pairs; and rotary diffusion about the helix axis to effect a migratory event. The model, which includes the possible role of electrostatic interactions, solves problems inherent in previous treatments. We find that no significant electrostatic torques arise that promote branch point migration. The absence of a kinetic mechanism to circumvent thermodynamic barriers due to mispairing suggests that an energy source is used for those situations in living systems.